HORMONAL AND BIO-CHEMICAL PROFILE AND EARLY PREGNANCY DIAGNOSIS BY ULTRASONOGRAPHY IN THOROUGHBRED MARES - RABARI, M L; SHAH, R G; TANK, P H; DHAMI, A J (The Indian Journal of Animal Reproduction, 2023)
This work was carried out on 45 Thoroughbred mares of private stud farm of North Gujarat during breeding season. The mares bred naturally were subjected to per rectal examination and ultrasonography for the pregnancy status and were divided into pregnant (n=35) and non-pregnant (n=10) groups. The pregnant mares were further distributed in three Groups as per the gestation days, viz., i) Group-I: mares between 0-35 days of gestation (n=12), ii) Group-II: mares between 36-75 days of gestation (n=12), iii) Group-Ill: mares between 76-150 days of gestation (n=11 ). The mean plasma progesterone level (ng/ml) of pregnant mares was significantly (P<0.01) higher in Group-Ill (29.32 ± 2.48) than in Group-I (17.29 ± 1.66) and II (23.62 ± 2.31), whereas in non-pregnant mares (Group-IV) it was significantly lower (1.68 ± 0.35). The mean plasma estradiol-17a level (pg/ml) was significantly higher (P< 0.05) in pregnant mares of Group-Ill (240.91 ± 32.13) than those in Group-I (91.92 ± 14.28), II (86.00 ± 7.15) and IV (74.50 ± 6.37). The mean plasma total cholesterol level (mg/di) was significantly (P<0.05) higher in non-pregnant mares than in pregnant mares of all three Groups. The mean plasma protein (g/dl) and glucose (mg/ di) levels did not differ significantly between various Groups of pregnant and non pregnant mares. The non-pregnant mares showed significantly higher mean plasma calcium level (mg/di) than the pregnant ones. The mean plasma phosphorus (mg/di) value was significantly higher in Group-Ill of pregnancy. The embryonic vesicle first became visible by ultrasonography as a fluid filled structure, recognized as non-echogenic sphere of 13.0 ± 4.0 mm on day 14 of pregnancy in 2 mares. The embryos as well as the fetal heart beats were detected for the first time on 28th day post-covering. The close relationships were observed between cholesterol and triglycerides, progesterone and estradiol, and gestation days with glucose level. In conclusion, the pregnancy can be diagnosed in Thoroughbred mares at the earliest on day 14th post-covering by scanning the embryonic vesicle, and around gestational days 76-150 by detecting higher levels of estradiol-17a (>155 pg/ml) and progesterone (>11 ng/ml).